Book Review: Menores, tutela estatal e instituciones de reforma. Buenos Aires (1890-1930), by María Carolina Zapiola - Fessler, Daniel (2020)
María Carolina Zapiola studies the transformation process which was registered in the childhood of popular sectors in the city of Buenos Aires. Based on her analysis of the confinement institutions in the Argentinian Capital during the end of the 19th and beginning of the 20th century, she reports how children are excluded and converted into «minors», a denomination or categorization which links them directly to criminal offences.